2009
DOI: 10.1086/605031
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Hospital‐Based Surveillance of Rotavirus Disease and Strains among Indian Children Aged <5 Years

Abstract: These data highlight the need for development and implementation of effective prophylactic measures, such as vaccines, to prevent the large burden of rotavirus disease among Indian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
78
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 22 publications
17
78
2
Order By: Relevance
“…Thus children below 1 year of age are found to be more susceptible to rotavirus infection and it may be due to lack of fully developed immune system. The results of the present study are in agreement with other previous reports (Sarvanan et al, 2004;Bahl et al, 2005;Kang et al, 2009). …”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 94%
See 1 more Smart Citation
“…Thus children below 1 year of age are found to be more susceptible to rotavirus infection and it may be due to lack of fully developed immune system. The results of the present study are in agreement with other previous reports (Sarvanan et al, 2004;Bahl et al, 2005;Kang et al, 2009). …”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 94%
“…Thus, analysis of season in relation to rotavirus infection from Punjab revealed a significant association of the occurrence of infection with cooler months. The results of the present study are comparable with previous studies (Saravanan et al, 2004;Bahl et al, 2005;Kang et al, 2009;Kaur, 2011), who have reported the pre-dominance of human rotavirus infection during cooler months in India. The correlation of rotavirus gastroenteritis with the age of the subject is studied by grouping the children of different age into eight groups, as depicted in (Table 1).…”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 92%
“…The Indian Rotavirus Strain Surveillance Network carried out a multi-centric study in seven different regions of India and reported that rotavirus was detected in stools of 39% children aged <5 years [3]. Inclusion of children at hospitals caring for lower acuity diarrheal episodes or less severe disease may account for a lower percentage of rotavirus positive cases among the total number of enrolled patients in our study compared with previous studies [3,[8][9][10][11][12][13][14][15].…”
Section: Fig 2 Monthly Distribution Of Rotavirus-positive Patients mentioning
confidence: 62%
“…Rotavirus is markedly seasonal in Northern temperate locations but was less seasonal in Southern locations with a tropical climate [3,10,17,18]. It has been observed that with minimal seasonality, rotaviruses circulate at a relatively higher level all year round, resulting in children being exposed at an early age and experiencing severe illness [14].…”
Section: Fig 2 Monthly Distribution Of Rotavirus-positive Patients mentioning
confidence: 99%
“…12,13 In a multicentric study conducted by Kang et al, rotavirus detection rates were greatest among children aged 6e23 months. 14 The association between seasonality and rotavirus diarrhea has not been clear with evidence both for and against it. 15,16 In our study, there was no statistically significant association of infection and time of the year, but the maximum percentage of rotavirus positive cases were recorded in the period from October to December (32.5%).…”
Section: Discussionmentioning
confidence: 99%